Creep Characteristics of Engineering Materials - Ta?ski, Tomasz; Sroka, Marek; Zieli?ski, Adam; Gola?ski, Grzegorz (IntechOpen, 2020)
This book contains chapters with the results of the research into the creep effect in different materials (ceramics, metallic materials, polymers, organic materials) and presents the method for using the assessment based on creep tests and numerical calculations to determine the actual lifetime. This subject has relevance as a significant development of new materials in which the creep effect is a decisive factor for their durability within the design service life have been observed in recent years. Therefore, there is a great demand for knowledge of the actual performance of materials during and beyond the design service life. The book aims to provide readers, including but not limited to MSc and PhD students as well as research personnel and engineers involved in operation of power equipment, with the comprehensive information on changes in the performance of creep-resistant materials during service.